2015
DOI: 10.1007/s00268-015-3186-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Loop Ileostomy Reversal: Is there an Advantage to a Minimally Invasive Approach?

Abstract: LIR is safe and effective with low perioperative morbidity and mortality. The use of laparoscopy as an option in terms of concomitant hernia repair and lysis of adhesions may be considered in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…10 Moreover, more recently, it is now conventional to conduct entirely laparoscopic procedures, and laparoscopic diverting ileostomy has been widespread and reported as a useful surgical procedure for low anterior resection of rectal cancer. 11,12 Although the closure of a colostomy or ileostomy requires less invasive surgery in general than the initial surgery, postoperative complications occur in 24.6% to 48% of cases overall. 13,14 Moreover, combining the closure of stoma in patients with risk factors including diabetes and obesity compels us to consider how we might mitigate complications as far as possible.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, more recently, it is now conventional to conduct entirely laparoscopic procedures, and laparoscopic diverting ileostomy has been widespread and reported as a useful surgical procedure for low anterior resection of rectal cancer. 11,12 Although the closure of a colostomy or ileostomy requires less invasive surgery in general than the initial surgery, postoperative complications occur in 24.6% to 48% of cases overall. 13,14 Moreover, combining the closure of stoma in patients with risk factors including diabetes and obesity compels us to consider how we might mitigate complications as far as possible.…”
Section: Discussionmentioning
confidence: 99%
“…studied adhesions in patients who underwent laparoscopy after a previous colectomy. They found fewer adhesions in patients who had previously undergone laparoscopic resections compared to those following open surgery, but multiple studies comparing adhesion formation after laparoscopic or open surgery have reported conflicting results both in animal models and in human studies …”
Section: Discussionmentioning
confidence: 99%
“…72 Regarding stoma reversal, laparoscopic ileostomy reversal has recently been proposed as an alternative to conventional open closure through the ileostomy site, with the benefit of laparoscopic hernia repair or prevention with mesh placement. In a retrospective cohort study comparing laparoscopic versus open ileostomy reversal in 53 patients versus 80 patients whose index case was performed either open, laparoscopically, or robotically, 73 the laparoscopic reversal group was associated with significantly longer operative time due to adhesiolysis and concurrent stoma site mesh reinforcement for hernia prevention. No conversion occurred in the laparoscopic group and no significant differences were noted in blood loss, LOS, or overall morbidity between the groups.…”
Section: Reoperative Minimally Invasive Surgery For Stoma Reversalmentioning
confidence: 99%
“…No conversion occurred in the laparoscopic group and no significant differences were noted in blood loss, LOS, or overall morbidity between the groups. 73 Unlike laparoscopic ileostomy closure, laparoscopic Hartmann's reversal has significant benefits over the open approach. In a systematic review of 35 studies on Hartmann's reversal in a total of 6,249 patients, 396 were reversed laparoscopically and 5,853 using an open approach.…”
Section: Reoperative Minimally Invasive Surgery For Stoma Reversalmentioning
confidence: 99%